(untitled) - Bùi, Đức Ái (Hanoi, 1962)
Tells us the story of Mrs Hậu, an ordinary woman of South VietNam during the Resitance war period
Keywords: Vietnamese literature,Văn học Việt Nam; 20th century,Thế kỷ 20